Solvent-desorption and regeneration of neutral, basic and acidic activated alumina from desulfurization of dibenzothiophene sulfone - Feliciano, Reyson M.; De Luna, Mark Daniel G.; Lu, Ming-Chun (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
Oxidized forms of Sulfur compounds such as DBTO are generally more removable than its parent compound from liquid fuel through adsorption. The challenge in adsorption technology has been focused on research for economic and environmental viability of adsorbent to be reusable and zero-waste capable. In this study, desorption parameters namely agitation, initial sulfur concentration, temperature, eluent type and eluent ratio were investigated on desorption of DBTO from neutral, basic, and acidic activated alumina. Desorption experimental data were fitted to pseudo-first order and pseudo-second order kinetic models of which the pseudo-second order kinetic model was found generally well fitted in at varying conditions of selected parameters from all adsorbents. Isotherm models that best describe the adsorption of DBTO from activated alumina by Freundlich isotherms over Langmuir isotherm implying heterogenous adsorption of DBTO on activated alumina active sites. Thermodynamic study showed spontaneity and endothermic process in the desorption of activated alumina at increasing temperature. The regeneration of neutral, acidic and basic activated alumina using 25 mL acetone with subsequent washing of 10 mL gained 96.5, 90.8 and 63.1% regeneration efficiency at second regeneration cycle, respectively. BET, XRD, FTIR and SEM analysis showed stable physicochemical properties of the regenerated adsorbents.
Thesis (Master of Science in Environmental Engineering)--University of the Philippines Diliman
Keywords: Desulfurization; Aluminum oxide; Adsorption